Alabama Governors : A Political History of the State - Webb, Samuel L., 1946-; Armbrester, Margaret E. (Margaret England), 1943- (Book collections on Project MUSE., 2014)
This collection of biographical essays, written by thirty-four noted historians and political scientists, chronicles the times, careers, challenges, leadership, and legacies of the fifty-seven men and one woman who have served as the state's highest elected official. The book is organized chronologically into six sections that cover Alabama's years as a US territory and its early statehood, the 1840s through the Civil War and Reconstruction, the late nineteenth-century Bourbon era, twentieth-century progressive and wartime governors, the Civil Rights era and George Wallace's period of inf.